Artificial pancreas techniques based on robust model predictive controller - Waleed Khalid Al-Azzawi (Institute of Advanced Engineering and Science, 2019)
Diabetes is known as the major cause of death in the world leading to kidney, retinopathy and cardiovascular diseases as well. In this paper, a Robust Model Predictive Controller (RMPC) is introduced to design artificial pancreas that solved the model uncertainty and keep the blood glucose level in the normal range by regulating the size of insulin infusion from pump based on RMPC. The simulation results will present a good performance of the proposed controller to avoid disturbance and robustness against uncertainties.